Interplay between vacancy-induced hydrogen segregation and stress-induced vacancy redistribution causing embrittlement of alpha-iron - Mugilgeethan Vijendran; Ryosuke Matsumoto (Science and Technology of Advanced Materials)
This study proposes a novel mechanism of intergranular fracture in alpha-iron, focusing on the effects of trapped vacancies, H atoms, and their synergistic interplay under tensile strain. We present a methodology for the introduction of H into grain boundaries (GBs) resulting in a realistic distribution by considering H – H interactions. Accordingly, optimal H concentrations were determined under specific environmental conditions for GBs with and without vacancy-induced segregation under zero and 2% tensile strain, respectively. Subsequently, the reduction in cohesive energy at GBs was evaluated at the optimal H concentration under these conditions. In the case of H segregation without vacancies at zero applied strain, the reduction in the cohesive energy ranged approximately from 15% to 35% for all the GB configurations. Eventually, vacancy segregation increased H concentration at the GBs, defined as vacancy-induced H segregation. The vacancy-induced H segregation resulted in a 60%–117% increase in H concentration and a 70%–80% decrease in cohesive energy at a vacancy concentration of [Formula: see text] under zero applied strain. The proposed vacancy-induced H-segregation mechanism explained the delayed fracture in steel. Furthermore, the effect of tensile strain on embrittlement was elucidated, with strain-induced vacancy redistribution and vacancy-induced H segregation synergistically promoting GB decohesion, resulting in a 73%–93% reduction in cohesive energy at the same vacancy concentration.